2003
DOI: 10.1002/ptr.1334
|View full text |Cite
|
Sign up to set email alerts
|

Pycnogenol® prevents haemolytic injury in G6PD deficient human erythrocytes

Abstract: Glucose6 phosphate dehydrogenase (G6PD) deficiency is the most common X-linked disorder of human erythrocytes where cells have inadequate capacity to destroy peroxides and high susceptibility towards haemolytic changes. Pycnogenol is a proprietary dry extract of the French Maritime pine (Pinus pinaster) bark with high ability to scavenge free radicals. In the present study we have investigated if Pycnogenol can protect G6PD deficient erythrocytes against haemolytic cell damage. Venous blood samples were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…It has been well documented that flavonoids from different sources including grape seed extract (Carini et (Zhu et al 2002), green tea (Zhang et al 1997) and pine bark extract (Sharma et al 2003) can offer protection against AAPH-induced and UVB-induced erythrocyte damage in vitro. The cocoa flavanols (epicatechin, catechin), Dimer B2 and 3 0 -O-methyl epicatechin all provided protective effects ( p , 0.001) against free radical-induced hemolysis in a dosedependent manner (2.5 mM-20 mM).…”
Section: Resultsmentioning
confidence: 99%
“…It has been well documented that flavonoids from different sources including grape seed extract (Carini et (Zhu et al 2002), green tea (Zhang et al 1997) and pine bark extract (Sharma et al 2003) can offer protection against AAPH-induced and UVB-induced erythrocyte damage in vitro. The cocoa flavanols (epicatechin, catechin), Dimer B2 and 3 0 -O-methyl epicatechin all provided protective effects ( p , 0.001) against free radical-induced hemolysis in a dosedependent manner (2.5 mM-20 mM).…”
Section: Resultsmentioning
confidence: 99%
“…Recent animal studies have shown that pycnogenol can inhibit histamine release from mast cells induced by compound 48/80 and Ionophore A-23187 (Sharma et al, 2003a) both of which are initiators of free radical formation (Akagi et al, 1998). Pycnogenol can also reduce cell toxicity caused by anti-tumour drugs (Feng et al, 2002) and protect G6PD (glucose 6 phosphate dehydrogenase) deficent human erythrocytes against haemolytic injury caused by ROS forming agents (Sharma et al, 2003b). Further work involving in vivo studies, however, should establish the usefulness of PYC in fluoride induced renal toxicity and may prove of some benefit in subjects constantly exposed to excessive environmental fluoride such as those living in endemic fluorosis areas (Lu et al, 2000;Griffin et al, 2002).…”
Section: Discussionmentioning
confidence: 97%
“…Most of the studies on the pharmacological activity of phytochemical components of Garcinia kola seed, have been on the biflavonoids. These phytochemicals have been shown to have a very broad spectrum of pharmacological activity: protective action against chemical induced hemolysis in G6PD deficient human red blood cells (Sharma et al, 2003); antiinflammatory antipyretic activity (Braide, 1993;Olaleye, 2000) inhibition of hepatic drug metabolism (Braide, 1991); antihepatotoxicity (Akintonwa and Essien, 1990;Iwu, 1985, Braide, 1991aAdegoke et al,1998;Adaramoye and Akinloye, 2000;Farombi, 2000;Farombi et al, 2000); hypoglycaemic anti-diabetic activity (Iwu et al, 1990); bronchodilatation in man (Orie and Ekon 1993); antispasmodic effect on smooth muscle (Braide, 1989); anti-thrombotic effect (Olajide, 1999).…”
Section: Introductionmentioning
confidence: 99%